Two new Hyphessobrycon (Characiformes: Characidae) species from Central Amazon basin, Brazil - Moreira, Cristiano R.; Lima, Flávio C.t. (Zootaxa, 2017)
Two new species of Hyphessobrycon, H. ericae and H. wosiackii, are described from the Amazon basin, Brazil. Both new species are distinguished from congeners by the coloration, composed by one humeral blotch merging with an anterior dark band restricted to the anterior portion of the body and the presence of a caudal peduncle blotch. Hyphessobrycon ericae is distinguished from H. wosiackii by presenting a humeral spot vertically elongated, with an overall appearance of an arrow, instead of an anteriorly rounded humeral spot.